Increasingly uneven intra-seasonal distribution of daily and hourly precipitation over Eastern China - Yang Chen (Environmental Research Letters, 2020)
It has been long appreciated that precipitation falls unevenly in time, but the degree of unevenness and its changes with warming have been seldomly quantified. These quantifications, however, matter to various sectors (e.g. crop and livestock yields) for addressing evolutionary hydro-meteorological hazards. Using gauge observations at hourly- and daily-resolution, precipitation unevenness is measured by the number of wettest days/hours for half of seasonal precipitation totals over Eastern China, a major breadbasket vulnerable to precipitation volatility intra-seasonally. Across the region, half of seasonal totals needs only 11 d or even more unexpectedly just 44 h to precipitate. During 1970–2017, though seasonal precipitation amount changed little, the intra-seasonal distribution of precipitation, in both frequency and amount, has been getting significantly more uneven, with more widespread and faster changes manifesting in hourly records. The regional-scale unevenness increase is unlikely modulated by internal variability alone, suggesting detectable contributions from anthropogenic climate change. The increased unevenness has led to significant lengthening of the longest dry spells, exposing the region to a more volatile precipitation mode—burstier-but-wetter storms with prolonged droughts in-between.